2016
DOI: 10.17957/tpmj/16.3215
|View full text |Cite
|
Sign up to set email alerts
|

Different Blood Groups; Association With Body Mass Index in Medical Students of Karachi

Abstract: ABSTRACT… Objectives: To find out the association of body mass index with different blood groups in medical students. Background: Increased body mass index leads to obesity and is a prominent risk factor for hypertension and diabetes. Blood groups are known to be associated with various diseases and recent studies have shown that a particular blood group with the highest body mass index appeared to be more susceptible to predisposition to hypertension. Study Design: Cross-sectional study. Setting: Liaquat Nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 1 publication
2
6
2
1
Order By: Relevance
“…Other studies from twin cities Islamabad and Rawalpindi [28], Gujranwala [29], Lahore [30], Mirpur [31] and Multan [32] reflects the same result like presented in this study of Safdarabad. The current findings of Faisalabad city where blood group O is found the most common is in agreement with the studies conducted in Multan [32], Karachi [33], and Gujrat [34] cities ( Table 3).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Other studies from twin cities Islamabad and Rawalpindi [28], Gujranwala [29], Lahore [30], Mirpur [31] and Multan [32] reflects the same result like presented in this study of Safdarabad. The current findings of Faisalabad city where blood group O is found the most common is in agreement with the studies conducted in Multan [32], Karachi [33], and Gujrat [34] cities ( Table 3).…”
Section: Discussionsupporting
confidence: 91%
“…The current findings of Faisalabad city where blood group O is found the most common is in agreement with the studies conducted in Multan [ 32 ], Karachi [ 33 ], and Gujrat [ 34 ] cities (Table 3 ).…”
Section: Main Textsupporting
confidence: 91%
“…This trend of result is similar to the report from studies by Acquaye [ 49 ] in Ghana and Eru et al [ 50 ] in Nigeria. Also, studies by Bhatti et al [ 51 ] in India and Parveen et al [ 30 ] as well as Bhattacharyya et al [ 52 ] in Pakistan have reported similar ABO blood group pattern. Worldwide distribution pattern has shown blood type O to be the most prevalent blood group followed by group B, group A, and group AB [ 53 ], which is consistent with the findings in this present study.…”
Section: Resultsmentioning
confidence: 69%
“…Reports in literature on the relationship between ABO blood group and BMI are inconsistent [ 38 , 56 ], with various authors associating increased BMI with the presence of particular ABO antigens, while others have shown no association between these two factors. Significant association was seen between ABO blood group and BMI among sampled populations from Pakistan [ 30 ], India [ 33 , 34 , 38 ], Malaysia [ 31 , 32 ], Nigeria [ 35 ], and Denmark [ 40 ]. One may be tempted to assume that ABO blood type and body weight may be biologically related probably through a pathway that involves thrombotic factors like FVIII because it is known for example, that non-blood group O individuals have higher FVIII.…”
Section: Resultsmentioning
confidence: 99%
“… 4 Several researchers in the past have reported the linkage of obesity with ABO blood groups, 4 , 5 while some have also disagreed to this relation. 2 , 6 Evidences are also present suggesting the ABO system as a genotype marker for obesity 7 but this relationship is still under intense investigation due to these conflicting results. New studies are needed to validate the association between blood groups and BMI, as the curiosity in this matter is unabated.…”
Section: Introductionmentioning
confidence: 99%